Secure in-session attachment predicts rupture resolution: negotiating a secure base - Miller-Bottome, Madeleine; Talia, Alessandro (Psychoanalytic psychology, 2019)
Decades of work by Jeremy Safran and his colleagues have established that ruptures in the therapeutic alliance are not necessarily obstacles to the treatment, and that the process of repairing these events has the potential to deepen the therapeutic relationship and promote change. The field of alliance rupture research has largely focused on therapists’ role in repairing ruptures or patient characteristics associated with greater rupture frequency, with little research on how the patient contributes to rupture repair. This study examines the predictive relationship between patients’ attachment and the report of the rupture resolution process over the course of treatment. Patients’ attachment was measured with the Patient Attachment Coding System (PACS), which assesses patients’ attachment as different ways of communicating about present internal experience during the session. Alliance ruptures were measured via self-report items on a postsession questionnaire. Results show that secure in-session attachment is associated with higher ratings of rupture repair, according to both patients and therapists, and that the link between secure in-session attachment and repair increased when ruptures were more intense. (PsycINFO Database Record (c) 2019 APA, all rights reserved)